Collection of initial and current control tests for 4th course students of medical and pediatric faculties content modules: gastroenterology, endocrinology, pulmonology, hematology, physiotherapy - Солов'юк, Олександр Олегович; Земляний, Ярослав Вадимович; Solovyuk, A. O.; Zemlyanoy, Ja.V. (Zaporizhzhya State Medical University, 2016)
Tests for assessment of current knowledge level were included in collection and appropriate programm of Internal Diseases (gastroenterology, endocrinology, pulmonology, hematology, physiotherapy ). The aim of this material is approvement of studying teoretical knowledge by 4th course students in accordance with Internal Diseases programm in VII-VIII semestres.
Keywords: internal diseases; gastroenterology; internal diseases; endocrinology; internal diseases; endocrinology; internal diseases; hematology; internal diseases; physiotherapy